Seated Position Does Not Change Lumbar Dimensions Compared With Lateral Position. Issue 1 (January 2022) - Long, Michael T.; Del Re, Angelo M.; Uya, Atim; Kanegaye, John T.; Nguyen, Margaret B.
Abstract : Objective: The infant lumbar puncture (LP) can be a technically challenging procedure. Understanding the anatomical lumbar dimensions may optimize LP conditions. Data from preterm neonates, older children, and adults indicate measurements of the lumbar spine in the seated LP position may be superior when compared with the lateral position. We use point-of-care ultrasound (US) to determine if the seated position, when compared with the lateral decubitus position, significantly affected the lumbar dimensions of infants 12 months or younger presenting to the pediatric emergency department. Methods: We conducted a prospective observational study of a convenience sample of patients 12 months or younger. We used US to obtain 3 still images oriented longitudinally in the midline over the L3 to L4 interspace in the lateral decubitus and seated positions. A US fellowship-trained emergency physician, blinded to patient position, measured interspinous space, subarachnoid space width, and spinal canal depth. We then compared the means of all 3 dimensions in the lateral and seated positions. Results: From 50 subjects, 49 subjects provided 46 evaluable sets of images for each measure. Interspinous space, spinal canal depth, and subarachnoid space width did not differ significantly between positions. Mean differences did not exceed 0.02 cm for any of the measured dimensions. We report no significant differences in the 3 lumbar dimensions at the seated position when compared with the lateral decubitus position. Conclusions: For infants younger than 12 months, sonographic measurements of lumbar dimensions did not differ between the positions commonly used for LP. Abstract : Supplemental digital content is available in the text.